FAKTOR PATOGENESIS DAN DIAGNOSIS PENYAKIT von Willebrand - R Sindunata; M. Y. Probohoesodo (Indonesian Association of Clinical Pathologist and Medical laboratory, 2006)
von Willebrand disease (vWD) is an autosomal inherited bleeding disorder caused by a deficiency or abnormality of von Willebrandfactor (vWF). vWF is a large multimeric glycoprotein that mediates platelet adhesion at the site of vessel injury. It also protects factorVIII from proteolytic degradation in the circulation. vWD has a prevalence of about 1% in the general population but less than 10%have bleeding symptoms. Bleeding symptoms are usually mucocutaneous and post surgical with varying severity. This disorder canresult from either a quantitative (types 1 and 3) or qualitative (type 2) defect in vWF. Type 2 vWD has been further classified into fourdistinct subtypes; 2A, 2B, 2M and 2N. The diagnosis of vWD requires attention to personal and family history of excessive bleeding andconfirmation by laboratory evaluation. A mild chronic thrombocytopenia is often seen in type 2B vWD. Patients with mild vWD oftenhave both a normal bleeding time and normal APTT. Specific tests for vWD diagnosis involve vWF antigen level, vWF activity (ristocetincofactor), and factor VIII activity. Once a diagnosis is established, additional tests that aid in classifying the type of vWD includeristocetin-induced platelet aggregation and vWF multimer analysis.